Financial management : principles and applications - Cabrera, Ma. Elenita Balatbat (Manila, Philippines : GIC Enterprises & Co. Inc., 2021)
Financial management, principles and applications is intended for use in a first course in financial management. It covers the essentials, fundamental concepts needed to help students develop finance literacy without becoming overwhelmed.
1. Overview of financial management -- 2. Evaluating operating and financial performance of business entity -- 3. Financial forecasting, planning and control -- 4. Working capital management -- 5. Long term investment decisions -- 6. Capital structure issues -- 7. Asset risks concepts and pricing -- Appendices -- List of references.
Includes bibliographical references.
Keywords: FINANCE